A clinical pilot study on the safety and efficacy of aerosol inhalation treatment of IFN-κ plus TFF2 in patients with moderate COVID-19. (August 2020) - Fu, Weihui; Liu, Yan; Xia, Lu; Li, Min; Song, Zhigang; Hu, Huiliang; Yang, Zongguo; Wang, Lin; Cheng, Xiaobo; Wang, Mei; Jiang, Rongrong; Liu, Li; et al.
Abstract: Background: The outbreak of a new coronavirus (SARS-CoV-2) poses a great challenge to global public health. New and effective intervention strategies are urgently needed to combat the disease. Methods: We conducted an open-label, non-randomized, clinical trial involving moderate COVID-19 patients according to study protocol. Patients were assigned in a 1:2 ratio to receive either aerosol inhalation treatment with IFN-κ and TFF2, every 48 h for three consecutive dosages, in addition to standard treatment (experimental group), or standard treatment alone (control group). The end point was the time to discharge from the hospital. This study is registered with chictr.org.cn, ChiCTR2000030262. Findings: A total of thirty-three eligible COVID-19 patients were enrolled from February 1, 2020 to April 6, 2020, eleven were assigned to the IFN-κ plus TFF2 group, and twenty-two to the control group. Safety and efficacy were evaluated for both groups. No treatment-associated severe adverse effects (SAE) were observed in the group treated with aerosol inhalation of IFN-κ plus TFF2, and no significant differences in the safety evaluations were observed between experimental and control groups. CT imaging was performed in all patients with the median improvement time of 5 . 0 days (IQR 3 . 0–9 . 0) in the experimental group versus 8 . 5 days (IQR 3 . 0–17 . 0) in the control group ( p <0 . 05). In addition, the experimental group had a significant shorten median time in cough relief (4 . 5 days [IQR 2 . 0–7 . 0]) than the control group did (10 . 0 days [IQR 6 . 0–21 . 0])( p <0 . 005), in viral RNA reversion of 6 . 0 days (IQR 2 . 0–13 . 0) in the experimental group vs 9.5 days (IQR 3 . 0–23 . 0) in the control group ( p < 0 . 05), and in the median hospitalization stays of 12 . 0 days (IQR 7.0–20.0) in the experimental group vs 15 . 0 days (IQR 10.0–25.0) in the control group ( p <0 . 001), respectively. Interpretation: Aerosol inhalation of IFN-κ plus TFF2 is a safe treatment and is likely to significantly facilitate clinical improvement, including cough relief, CT imaging improvement, and viral RNA reversion, thereby achieves an early release from hospitalization. These data support to explore a scale-up trial with IFN-κ plus TFF2. Funding: National Major Project for Control and Prevention of Infectious Disease in China, Shanghai Science and Technology Commission, Shanghai Municipal Health Commission.